1955
DOI: 10.3181/00379727-88-21637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dextran Edema by Proteolytic Enzymes

Abstract: 517 the concentration of K+ or Na+ was 0.1 M or more. Also, the smaller amount of alkali required to adjust maleate buffer to pH 5.5 than to 7.9 or 7.0 may have augmented the inhibition reported by him at pH 5.5 because of the lower ionic strength; however, our results indicate, as do his, greater inhibition at acid pH values. The splitting of ATP by U02C12 may have had bearing upon his failure to detect inhibition at pH 7.9. This is especially likely if he used long incubations.1. It has been demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1958
1958
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
4
0
1
Order By: Relevance
“…It has been reported that the anti-inflamma tory activity of the proteolytic enzymes, such as a-chymotrypsin do not appear to be medi ated by stimulation of the pituitary-adrenal axis (5,25), since the anti-inflammatory effects remain after adrenalectomy. In tire present experiment, the plasma corticosterone level was markedly raised after intravenous injection of P-10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the anti-inflamma tory activity of the proteolytic enzymes, such as a-chymotrypsin do not appear to be medi ated by stimulation of the pituitary-adrenal axis (5,25), since the anti-inflammatory effects remain after adrenalectomy. In tire present experiment, the plasma corticosterone level was markedly raised after intravenous injection of P-10.…”
Section: Discussionmentioning
confidence: 99%
“…In most investigations on the anti-inflamma tory effect of proteolytic enzymes, the preven tive effect of protease is evaluated after intra peritoneal (5,26) or subcutaneous (14) admin istration. In either case, severe inflammation occurs at the injected sites and this may be responsible for a nonspecific 'inhibitory effect' (8,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aux oedèmes généralisés déclenchés par injection de dextran (4,5,16) qui se prêtent mal à une mesure précise de l'effet pro tecteur des drogues, nous avons préféré une action phlogistique locale. Cette action est habituellement développée sur deux es pèces : le rat et le cobaye.…”
unclassified
“…It has been reported that anti-inflamma tory activity of proteolytic enzymes such as trypsin [Cohen et al, 1955;Martin et al, 1954], a-chymotrypsin [Martin et al, 1954;Miecowski and Ercoli, 1956;Yokoyama et al, 1975], may not be related to the adrenal gland, since a remarkable anti-inflammatory effect has been shown in adrenalectomized rats [Cohen et al, 1955;Yamasaki et al. 1967], Recently, it has been proved that when Prozime-10 (P-10), a serine protease extracted from cultured broth of Aspergillus malleus [Ito and Sugiura, 1968;Nagalani, 1966], is effective in various experimental inflammations [Tasaka et al.…”
Section: Introductionmentioning
confidence: 99%